2016
DOI: 10.2217/ije-2016-0006
|View full text |Cite|
|
Sign up to set email alerts
|

The ENETS/WHO Grading System for Neuroendocrine Neoplasms of the Gastroenteropancreatic System: A Review of the Current State, Limitations and Proposals for Modifications

Abstract: The understanding of neuroendocrine neoplasms has evolved significantly since their initial descriptions in the 1800s to early 1900s. In the gastroenteropancreatic system, this group of malignant tumors is subdivided into well and poorly differentiated neuroendocrine neoplasms based on morphologic, proliferative and biologic differences. However, it has become increasingly apparent that well-differentiated neuroendocrine tumors are not a homogeneous group. Attempting to better predict outcome of these tumors h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 110 publications
1
28
0
Order By: Relevance
“…They found that p-NENs with a Ki-67 proliferative index > 20%, if well-differentiated, were more aggressive than G2 but significantly less aggressive than “G3 p-NECs” with poorly differentiated features (large or small cell type) [ 22 ]. Furthermore, the WHO 2010 grading classification just used the terminology “high-grade” and “poorly-differentiated” interchangeably for neoplasms in the G3 category, while recent studies have further focused on the heterogeneity of “G3 p-NECs”, in which some might primarily present a high Ki-67 proliferative rate but be morphologically well-differentiated [ 23 ]. Sorbye et al demonstrated the WHO 2010 “G3 p-NECs” were morphologically and biologically heterogenous, in which they reported a lower response rate after platinum-based systemic chemotherapy (15% vs. 42%, respectively; P < 0.05), but a longer MST (14mon vs. 10mon, respectively; P < 0.05) among tumors with a Ki-67 < 55%, compared with those having a higher Ki-67 index [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…They found that p-NENs with a Ki-67 proliferative index > 20%, if well-differentiated, were more aggressive than G2 but significantly less aggressive than “G3 p-NECs” with poorly differentiated features (large or small cell type) [ 22 ]. Furthermore, the WHO 2010 grading classification just used the terminology “high-grade” and “poorly-differentiated” interchangeably for neoplasms in the G3 category, while recent studies have further focused on the heterogeneity of “G3 p-NECs”, in which some might primarily present a high Ki-67 proliferative rate but be morphologically well-differentiated [ 23 ]. Sorbye et al demonstrated the WHO 2010 “G3 p-NECs” were morphologically and biologically heterogenous, in which they reported a lower response rate after platinum-based systemic chemotherapy (15% vs. 42%, respectively; P < 0.05), but a longer MST (14mon vs. 10mon, respectively; P < 0.05) among tumors with a Ki-67 < 55%, compared with those having a higher Ki-67 index [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…They found that p-NENs with a Ki-67 proliferative index > 20%, if well-differentiated, were more aggressive than G2 but signi cantly less aggressive than "G3 p-NECs" with poorly differentiated features (large or small cell type) [20] . Furthermore, the WHO 2010 grading classi cation just used the terminology "high-grade" and "poorly-differentiated" interchangeably for neoplasms in the G3 category, while recent studies have further focused on the heterogeneity of "G3 p-NECs", in which some might primarily present a high Ki-67 proliferative rate but be morphologically well-differentiated [21] . Sorbye et al demonstrated the WHO 2010 "G3 p-NECs" were morphologically and biologically heterogenous, in which they reported a lower response rate after platinum-based systemic chemotherapy (15% vs. 42%, respectively; P < 0.05), but a longer MST (14mon vs. 10mon, respectively; P < 0.05) among tumors with a Ki-67 < 55%, compared with those having a higher Ki-67 index [22] .…”
Section: Discussionmentioning
confidence: 99%
“…They found that p-NENs with a Ki-67 proliferative index > 20%, if well-differentiated, were more aggressive than G2 but significantly less aggressive than "G3 p-NECs" with poorly differentiated features (large or small cell type) [20] . Furthermore, the WHO 2010 grading classification just used the terminology "high-grade" and "poorly-differentiated" interchangeably for neoplasms in the G3 category, while recent studies have further focused on the heterogeneity of "G3 p-NECs", in which some might primarily present a high Ki-67 proliferative rate but be morphologically well-differentiated [21] . Sorbye et al demonstrated the WHO 2010 "G3 p-NECs" were morphologically and biologically heterogenous, in which they reported a lower response rate after platinum-based systemic chemotherapy (15% vs. 42%, respectively; P < 0.05), but a longer MST (14mon vs. 10mon, respectively; P < 0.05) among tumors with a Ki-67 < 55%, compared with those having a higher Ki-67 index [22] .…”
Section: Discussionmentioning
confidence: 99%